2002
DOI: 10.1590/s1519-566x2002000100002
|View full text |Cite
|
Sign up to set email alerts
|

Electroantennographic responses of the Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva) (Diptera: Psychodidae) to 1-octen-3-ol

Abstract: Respostas Eletroantenográficas de Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva) (Diptera: Psychodidae) a 1-octen-3-ol RESUMO-Octenol (1-octen-3-ol) é um cairomônio utilizado por vários grupos de insetos hematófagos para a localização de hospedeiros vertebrados. No entanto, o seu efeito sobre Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva) nunca foi estudado. O presente trabalho avaliou as respostas eletroantenográficas (EAG) de fêmeas de L. longipalpis. Como estímulo controle utilizou-se corrente de ar, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…El Octenol se encuentra también en maíz y chicharo de vaca, aunque en menor concentración (Gouinguene, 2005). Este compuesto ha sido evaluado ampliamente como un kairomona (Sant'Ana et al, 2002) en los insectos hematófagos porque se encuentra en diferentes fuentes, tales como el aliento de los bovinos y de los humanos (Torres et al, 2014;Torto, 2002Torto, -2015, especificamente el mosco Lutzomyia longipalpis es capaz de detectar el 1-octen-3-ol en corrientes de aire (Sant'Ana et al, 2002;Lazzari, 2011). Debido a la eficiencia de atracción con mosquitos es considerado un control eficiente de las enfermedades transmitidas por este tipo de vectores (Laporta y Sallum, 2011).…”
Section: Resultados Y Discusiónunclassified
“…El Octenol se encuentra también en maíz y chicharo de vaca, aunque en menor concentración (Gouinguene, 2005). Este compuesto ha sido evaluado ampliamente como un kairomona (Sant'Ana et al, 2002) en los insectos hematófagos porque se encuentra en diferentes fuentes, tales como el aliento de los bovinos y de los humanos (Torres et al, 2014;Torto, 2002Torto, -2015, especificamente el mosco Lutzomyia longipalpis es capaz de detectar el 1-octen-3-ol en corrientes de aire (Sant'Ana et al, 2002;Lazzari, 2011). Debido a la eficiencia de atracción con mosquitos es considerado un control eficiente de las enfermedades transmitidas por este tipo de vectores (Laporta y Sallum, 2011).…”
Section: Resultados Y Discusiónunclassified
“…A related study also using a Y‐tube system demonstrated that low concentrations of 1‐octen‐3‐ol are attractive to Simulium ornatum Meigen (Opoku, ), corroborating the findings in S. vittatum reported here. Although 1‐octen‐3‐ol is attractive to numerous families of nematoceran or brachyceran dipterans (Hall et al ., ; Gibson & Torr, ; Bhasin et al ., ; Sant'Anna et al ., ; Birkett et al ., ; Harrup et al ., ), this compound was not attractive to some Nearctic simuliids [ Simulium meridionale Riley and Cnephia pecuarum (Riley)] in comparison with CO 2 alone under field conditions (Atwood & Meisch, ). In fact, these authors suggested that its use in traps may impair sampling of certain blackfly species.…”
Section: Discussionmentioning
confidence: 99%
“…longipalpis females than did the hexane used as control treatment (Bray and Hamilton 2007). Santana et al (2002) demonstrated the attraction of Lu. longipalpis to 1-octen-3-ol (octenol) in air currents.…”
mentioning
confidence: 92%